Associations between sexual partner number and HIV risk behaviors: implications for HIV prevention efforts in a Treatment as Prevention (TasP) environment. Issue 10 (3rd October 2018) - Armstrong, Heather L.; Roth, Eric Abella; Rich, Ashleigh; Lachowsky, Nathan J.; Cui, Zishan; Sereda, Paul; Card, Kiffer G.; Jollimore, Jody; Howard, Terry; Moore, David M.; Hogg, Robert S.
ABSTRACT: Previous research indicates that gay and bisexual men (GBM) have significantly more sexual partners than same-aged heterosexual men and women. As a result, some HIV intervention programs have focused on partner reduction. However, new research findings question the relevance of sexual partner number as a sexual risk measure for GBM given Treatment as Prevention (TasP) programs and new seroadaptive strategies which have led to lower GBM community viral load and new HIV prevention behaviors. To assess if sexual partner number continues to remain an important measure of sexual risk for GBM living in a city that actively promotes TasP as provincial policy, we analysed cross-sectional data from 719 GBM recruited through respondent-driven sampling in Vancouver, Canada. Multivariable negative binomial regression analysis showed that partner number was significantly associated with previously identified HIV risk factors including condomless anal intercourse with serodiscordant and/or unknown serostatus partners, using sex toys, attending group sex events, receiving money for sex, and sex drug use. These results indicate that sexual partner number remains an important proximate HIV risk measure. However, more nuanced measures of HIV treatment status and greater understanding of the possible causes of increased partner number among GBM are needed.